Dimeric quinacrines as chemical tools to identify PPT1, a new regulator of autophagy in cancer cells - Michael C. Nicastri; Vito W. Rebecca; Ravi K. Amaravadi; Jeffrey D. Winkler (Molecular & Cellular Oncology, 2018)
DQ661 is a novel dimeric quinacrine that affects multiple lysosomal functions (autophagy and macropinocytosis) and mTORC1 (mechanistic target of rapamycin) activity by specifically targeting protein-palmitoyl thioesterase 1 (PPT1). DQ661 has in vivo activity in immunocompetent mouse models of cancer, and constitutes a new tool compound for the study of lysosomal function in cancer and therapeutic resistance.